2018
DOI: 10.1039/c8ra00171e
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of polymers on the properties of hydrogels constructed using sodium deoxycholate and amino acid

Abstract: The gelation behavior and properties of sodium deoxycholate (NaDC) and L-aspartic acid (Asp) in aqueous solution were investigated in detail at 25 C. The linear polymer poly(2-(2-methoxyethoxy)ethyl methacrylate-co-oligo-(ethylene glycol) methacrylate) (P(MEO 2 MA 90 -co-OEGMA 10 )) and star-shaped polymer poly(2-(dimethylamino)ethyl methacrylate-b-2-(2-methoxyethoxy)ethyl methacrylate) (CDPDPM) were introduced in NaDC/Asp hydrogels for exploring the effects of polymers on the properties of NaDC/Asp hydrogels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…As we all know the anionic surface active agent NaDC is usually used as gelatinizing agent for immobilizing biomolecules owing to its special rigid structure and good biocompatibility [39]. In the present study, NaDC was selected as the substitute of the ILs to prepare the NaDC-PPy/GCE and the corresponding conductivity was further studied.…”
Section: Resultsmentioning
confidence: 99%
“…As we all know the anionic surface active agent NaDC is usually used as gelatinizing agent for immobilizing biomolecules owing to its special rigid structure and good biocompatibility [39]. In the present study, NaDC was selected as the substitute of the ILs to prepare the NaDC-PPy/GCE and the corresponding conductivity was further studied.…”
Section: Resultsmentioning
confidence: 99%
“…It was earlier shown that cationic polymers and lipids can alter the infectivity of rAAV 19, 20, 21, 22. It is conceivable that more than a 20% transduction increase for rAAV5 after Na-DC treatment is caused by detergent residuals in the sample, especially given that Na-DC is known to form polymers 23 …”
Section: Discussionmentioning
confidence: 99%
“…Participation of the polymers in the gelation process increased the density of gel network resulting in an increase in the mechanical strength of the hydrogel. [129] Besides using various external modifiers, researchers have also performed several of structural modifications in bile salts to alter the gelation properties. For example, Maitra and co-workers have reported the synthesis of bile salt derivatives through addition of some functional groups.…”
Section: Natural Bile Salt Based Gelatorsmentioning
confidence: 99%
“…have studied the effect of a linear and a star shaped polymer on the morphological, optical, and rheological properties of NaDC‐L‐aspartic acid hydrogel. Participation of the polymers in the gelation process increased the density of gel network resulting in an increase in the mechanical strength of the hydrogel [129] . Besides using various external modifiers, researchers have also performed several of structural modifications in bile salts to alter the gelation properties.…”
Section: Natural Bile Salt Based Gelatorsmentioning
confidence: 99%